The Emergence of New Regional Convergence Clubs in a Nordic and Baltic Perspective - Andreas P. Cornett; Nils Karl Soerensen (European Regional Science Association (ERSA), 2010)
The spatial patterns of changes in economic diversion and convergence have become more blurred in the last decades. International disparities between nations have diminished. At the same time intra-national disparities have increased in most European countries. In the search to identify the drivers behind this seemingly paradox this paper tries to look behind the traditional way to analyze convergence and disparities based on consolidated national or geographical based groups of regions. The purpose of the paper is to identify groups or clubs of regions in the Nordic countries characterized by similar patterns of development with regard to economic performance measured by GDP per capita. The clubs are identified by a series of variables defined according to the most important determinants for economic growth according to neoclassical and new economic growth theory, i.e. capital formation, labor force, but also innovative capabilities, human resources, entrepreneurship etc. The first section provides a brief outline of the theoretical foundations and a discussion of the specific research questions analyzed. Section 2 provides a survey of regional growth performance with special attention on divergence and convergence based on NUTS II or similar regional division based on statistics ranging from the mid 1990ties. Section 3 aims to identify different types of regions according to the main drivers of regional change. The following factors are examined: Population change and composition, regional innovative potential and entrepreneurial behavior. Based on this identification of regional clubs, challenges and tendencies of regional development are assessed in a spatial and national context. The last section summarizes the main findings of the study and provides an attempt to characterize the spatial and structural characteristics of the identified groups. Finally an attempt is made to sketch some further perspectives and policy implications of the obtained results.
Keywords: R11; R12; R58; 330; economic convergence and disparities; growth drivers; convergence clubs; typology of regions